A chance encounter in central Texas yields insights on the ecology of aestivating Siren nettingi (Caudata: Sirenidae) - Sirsi, Shashwat; Zughaiyir, Ferris E.; Villamizar-Gomez, Andrea; Bohannon, Austin M. A.; Forstner, Michael R. J. (Phyllomedusa: Journal of Herpetology, 2023)
Siren spp. are often dominant vertebrates in the wetlands they occupy and are known to estivate when such wetlands dry up. Practical considerationslimit in-situ observations of estivating individuals. On 12 October 2021, we incidentally discovered an estivating aggregate of Siren nettingi in Bastrop County, Texas, USA. These salamanders were excavated from compact, rocky soil adjacent to a caliche road, at depths that ranged between ~0.2 to 1.5 m. The dominant vegetation at this site included Ulmus crassifolia, Persicaria sp., and various grass species. We recovered 140 individuals of which seven were salvaged and 133 were captured live. We measured 115 of these for snout–vent length (SVL) and observed the aggregate was predominated by juveniles. We estimated an estivation density of 2.33 sirens/m2 that is comparable to densities estimated for non-estivating populations. However, in-lieu of monitoring that was in place for this study, we expect a mass mortality event would have likely occurred. We therefore suggest that roadway construction in preferred habitat be considered as a threat to siren populations.